Autonomy in Depressive Patients Undergoing DBS-Treatment: Informed Consent, Freedom of Will and DBS’ Potential to Restore It - Beeker, Timo; Schlaepfer, Thomas E.; Coenen, Volker A. (Frontiers in Integrative Neuroscience, 2017)
According to the World Health Organization, depression is one of the most common and most disa-bling psychiatric disorders, affecting at any given time approximately 325 million people worldwide. As there is strong evidence that depressive disorders are associated with a dynamic dysregulation of neural circuits involved in emotional processing, recently several attempts have been made to inter-vene directly in these circuits via deep brain stimulation (DBS) in patients with treatment-resistant major depressive disorder (MDD). Given the promising results of most of these studies, the rising medical interest in this new treatment correlates with a growing sensitivity to ethical questions. One of the most crucial concerns is that DBS might interfere with patients’ ability to make auton-omous decisions. Thus, the goal of this article is to evaluate the impact DBS presumably has on the capacity to decide and act autonomously in patients with MDD in the light of the autonomy-undermining effects depression has itself. Following the chronological order of the procedure, special attention will first be paid to depression’s effects on patients’ capacity to make use of their free will in giving valid Informed Consent. We suggest that while the majority of patients with MDD appear capable of autonomous choices, as it is required for Informed Consent, they might still be unable to effectively act according to their own will whenever acting includes significant personal effort. In reducing disabling depressive symptoms like anhedonia and decrease of energy, DBS for treatment resistant MDD thus rather seems to be an opportunity to substantially increase autonomy than a threat to it.